An economic assessment of soil carbon sequestration with biochar in Germany - Isabel Teichmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Biochar is a carbon-rich solid obtained from the heating of biomass in the (near) absence of oxygen in a process called pyrolysis. Its soil incorporation is increasingly discussed as a means to sequester carbon in soils and, thus, to help mitigate climate change. When deployed in agricultural soils in Germany, it has been found by Teichmann (2014a, b) that slowpyrolysis biochar from a wide variety of feedstocks - together with the use of the pyrolysis by-products (liquids and gases) as renewable sources of energy - could lead to an annual mitigation of up to 10.2 million tonnes of carbon-dioxide equivalents by 2030 and of up to 10.6 million tonnes by 2050. To analyze whether this technically feasible greenhouse-gas mitigation potential is also economically viable, we calculate the corresponding greenhousegas mitigation costs and construct so-called marginal abatement cost curves. Thereby, we find that about 3.1 million tonnes of carbon-dioxide equivalents could be abated in 2030 at costs below exteuro201245 per tonne of carbon dioxide and nearly 3.8 million tonnes in 2050 at costs below exteuro201275 per tonne of carbon dioxide.
Keywords: Q15; Q24; Q54; 330; biochar; agriculture; Germany; climate change; soil carbon sequestration; mitigation costs; marginal abatement cost curves